Inheritance of resistance to wheat streak mosaic virus in wheat line KS06HW79 - Curato, John (Kansas State University, 2016)
Wheat streak mosaic virus (WSMV) is a disease that causes significant yield losses in wheat (Triticum aestivum L.). Host resistance is the primary approach for control. KS06HW79 is a wheat line with WSMV resistance up to 21°C. To study the inheritance of resistance in KS06HW79, it was crossed with two WSMV-susceptible wheat genotypes, KS020638-M-5 and Brawl CL Plus. Parental lines, F₁, F₂, and check varieties were mechanically inoculated and evaluated for WSMV resistance at 21°C in growth chambers. The segregation pattern in two F₂ populations fit a one-recessive-gene model (1 resistant : 3 susceptible) and a dominant-suppression-epistasis model (3 resistant : 13 susceptible). To determine which model was a better fit, WSMV resistance was evaluated for F₂:₃ families generated from resistant F₂ plants in both crosses. Approximately two thirds of the F₂:₃ families in each cross showed segregation for WSMV resistance, suggesting that the dominant-suppression epistasis model better explained the WSMV resistance in KS06HW79. This model was also supported by two KS06HW79-derived doubled haploid populations, which had a segregation ratio of 1 resistant : 3 susceptible. Therefore, the WSMV resistance in KS06HW79 is likely controlled by two dominant genes, one of which is a suppressor.
Keywords: wheat streak mosaic virus; dominant suppression epistasiswheat